EFEKTIVITAS MODEL PEMBELAJARAN ASSURE BERBANTU MEDIA STORYBOARD TERHADAP KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK KELAS IV SD NEGERI 22 TULANG BAWANG UDIK - Tania Afrilia; Nurul Hidayah; Ayu Reza Ningrum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is based on the low critical thinking skills of students in the science subject of grade IV at SD Negeri 22 Tulang Bawang Udik. Students tend to be passive and less active during the learning process, thus having an impact on low learning outcomes, especially critical thinking skills. To overcome this problem, the ASSURE learning model combined with STORYBOARD media was applied in the hope of increasing students' activeness and critical thinking skills. The formulation of the problem in this study is whether the use of the ASSURE learning model assisted by STORYBOARD media is effective on students' critical thinking skills. This study aims to determine the effectiveness of the model in grade IV students.The research uses a quantitative approach with the type of Quasi Experiment Design and Non Equivalent Control Group Design. The sample amounted to 43 students, namely 20 students of class IV B as a control class using the PBL model and 23 students of class IV A as an experimental class using the ASSURE model assisted by STORYBOARD media. The data collection instruments were in the form of pretest and posttest with 10 description questions. Data were analyzed using a t-test after meeting the prerequisite tests for normality and homogeneity. The results showed a significance value of 0.000 < 0.05, so there was a significant difference between the posttest value of the experimental and control classes. Thus, H0 is rejected and H1 is accepted. The study concluded that the ASSURE learning model assisted by STORYBOARD media was effective in improving the critical thinking skills of grade IV students.